TRADISI PATRIARKI, TINGKAT PENDIDIKAN, LINGKUNGAN KELUARGA: DAMPAKNYA TERHADAP KEMISKINAN FEMINISME PADA MASYARAKAT BATAK TRADISIONAL - Handayani, Juwita; Lubis, Abdul Latif; Makhrani, Makhrani; Lubis, Lilis Suryani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to examine the influence of patriarchal traditions, education levels, and family environments on feminist poverty in Batak society. Strong patriarchal culture places women in a subordinate position, limiting their rights in decision-making, education, and economic access. The results show that Batak women face cultural challenges that reinforce economic dependence on men, limited inheritance rights, and low priority of education for women. In addition, the family environment plays a significant role, both as a reinforcement of poverty through oppressive norms, and as a supporter when providing access to education and economic freedom. Feminist poverty in Batak society is not only in the form of low income, but also includes limited access to resources, health, and education, as well as social stigma that worsens the situation of women. This study emphasizes the importance of customary reform, increasing public awareness of gender equality, and inclusive education and economic policies as an effort to break the cycle of feminist poverty. These results are in line with Connell's patriarchal theory and Sen's views on the role of education in women's empowerment, and show the relevance of Bourdieu's social capital in shaping women's economic opportunities